Pengaruh sisi aliran masuk terhadap prestasi pompa sebagai turbin dengan jumlah sudu bervariasi - Asral (BKS-TM Indonesia, 2025)
Pump as Turbine (PAT) is an innovative solution in generating small-scale electrical energy in rural areas. However, the performance of PAT is strongly influenced by the configuration of the impeller, especially the number of blades that can affect the efficiency and electrical output power. Therefore, this study aims to analyze the effect of inflow and variation in the number of impeller blades on the performance of PAT as a picohydro power plant. This research was conducted experimentally in the laboratory using three different types of impellers, each having 9, 10, and 12 blades. Tests were conducted at various levels of valve opening ranging from 50%, 66.6%, 83.3% and 100% opening. The test results were then analyzed based on system efficiency, water flow rate, and electricity generated. The results showed that the impeller with the number of blades 10 produced the highest efficiency which reached 78% at 100% valve opening, while the impeller with the number of blades 12 showed the lowest efficiency due to greater water flow resistance. The highest electrical power is generated by the number of blades 10 with an output of 258.74 Watts. Thus, the selection of the optimal number of blades is very important to improve the performance of PAT as an efficient and economical renewable energy solution